PERANCANGAN LOGO DAN BRANDING UNTUK MENINGKATKAN DAYA TARIK DAN NILAI JUAL UMKM DI DESA SIRNAJAYA - Mubarok, Syahrul; Dewi Cahyati, Ari; Putra, Purnama (Universitas Islam 45 Bekasi, 2024)
Numerous MSMEs are developing and creating in Bekasi, such as in Serangbaru, particularly in Sirnajaya village, one of the regions in West Java area with geographical conditions that have very huge potential within the areas of agriculture and industry. Observations were carried out amid this socialization to discover out how innovation is creating in Sirnajaya village. In any case, numerous MSMEs in Sirnajaya village tend to have a advertise reach that's still nearby since they don't however have business identity and items that can be recognized by the more extensive community. Logos and branding are characters that can be utilized as apparatuses to recognize items and businesses, but to utilize logos and bundling you must pay attention to the components in realistic plan so that you simply can create a symbol with appealing branding. The significance of a symbol for MSMEs is one of the critical things for a company or your commerce. Having a symbol can reflect the personality of the company itself so that it is superior known to numerous individuals, in this manner building a brand is critical in beginning a trade.